Infinite Golden Sum

Algebra Level 4

What is the value of the following infinite sum?

ϕ n + ϕ n 1 + ϕ n 2 + . . . \phi^n+\phi^{n-1}+\phi^{n-2}+... , where n n is an integer.

ϕ \phi is the golden ratio .

ϕ n + 1 \phi^{n+1} ϕ \phi ϕ n + 2 \phi^{n+2} This series diverges ϕ n + 3 \phi^{n+3}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Oct 25, 2018

S = φ n + φ n 1 + φ n 2 + where φ is golden ratio. = φ n k = 0 φ k Sum of an infinite geometric progression = φ n 1 1 φ 1 = φ n φ φ 1 Note that φ 2 φ 1 = 0 = φ n φ 2 1 φ 1 φ = φ 2 1 = φ n ( φ 1 ) ( φ + 1 ) φ 1 = φ n ( φ + 1 ) and φ 2 = φ + 1 = φ n + 2 \begin{aligned} S & = \varphi^n + \varphi^{n-1} + \varphi^{n-2} + \cdots & \small \color{#3D99F6} \text{where }\varphi \text{ is golden ratio.} \\ & = \varphi^n \color{#3D99F6} \sum_{k=0}^\infty \varphi^{-k} & \small \color{#3D99F6} \text{Sum of an infinite geometric progression} \\ & = \varphi^n \cdot \color{#3D99F6} \frac 1{1-\varphi^{-1}} \\ & = \varphi^n \cdot \frac {\color{#3D99F6}\varphi}{\varphi -1} & \small \color{#3D99F6} \text{Note that }\varphi^2 - \varphi - 1 = 0 \\ & = \varphi^n \cdot \frac {\color{#3D99F6}\varphi^2-1}{\varphi -1} & \small \color{#3D99F6} \implies \varphi = \varphi^2 - 1 \\ & = \varphi^n \cdot \frac {(\varphi-1)(\varphi + 1)}{\varphi -1} \\ & = \varphi^n \color{#3D99F6} (\varphi + 1) & \small \color{#3D99F6} \text{and }\varphi^2 = \varphi + 1 \\ & = \boxed{\varphi^{n+2}} \end{aligned}

We have a infinite Geometric Progression with common ratio 1 ϕ \frac{1}{\phi} . This common ratio is smaller than 1 1 , so we can use the infinite GP sum formula:

S = a 1 r S=\frac{a}{1-r} , where S S is the limit of the series, a a is the first term of the GP and r r is the common ratio. Substituting:

S = ϕ n 1 1 ϕ S=\frac{\phi^n}{1-\frac{1}{\phi}}

S = ϕ n ϕ 1 ϕ S=\frac{\phi^n}{\frac{\phi-1}{\phi}}

S = ϕ n + 1 ϕ 1 S=\frac{\phi^{n+1}}{\phi-1}

By the properties of the golden ratio we have that ϕ 1 = 1 ϕ \phi-1=\frac{1}{\phi} . Hence:

S = ϕ n + 1 1 ϕ S=\frac{\phi^{n+1}}{\frac{1}{\phi}}

S = ϕ n + 2 S=\phi^{n+2}

Then the final answer is ϕ n + 2 \boxed{\phi^{n+2}} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...